Public Debt of Japan: Analysis of Features and Assessment of Prospects - R. B. Nozdreva (Vestnik MGIMO-Universiteta, 2019)
The article describes the current state of Japan's public debt, which exceeds its GDP by almost 2.5 times; it seeks to identify the main causes for its growth, analyses its structure, reviews the main stages of its formation; assesses the effectiveness of government measures to regulate it and makes a comparative analysis with the national debt of the United States.The distinctive nature of Japan's public debt is that it is based on the relative stability of Japan’s financial system and a high degree of trust in it both domestically and abroad. In particular, the sustainability of the debt is ensured by the fact that 95% of government bonds are owned by residents. Despite the pessimistic mood of the IMF, investors continue to actively acquire debt obligations of the Japanese government. The behavior of investors is affected by the strengthening of the position of Neo-Keynesians in world economic sci ence, who consider domestic debt safe, assuming that budget expenditures can be equal to the sum of tax revenues and domestic debt. Government bonds will continue to play a dominant role in the Japanese debt market for a long time and, although the volume of this type of loans is large, a high degree of confidence in Japanese finances will remain both domestically and abroad thanks to a competent, cautious and conservative financial policy. In the field of public debt regulation, the author considers the Bank of Japan's policy to be successful, it mitigates the negative impact of public debt on the development of the Japanese economy. On the contrary, the effectiveness of government measures, including the Three Arrows Plan of Prime Minister S. Abe, is assessed as non-effective. Government spending is growing, but the government does not introduce restrictive measures of debt policy, considering that an annual increase in government debt by 1% is necessary to maintain economic growth. Based on the study, a forecast is made that Japan will maintain a high level of public debt for the next five years.